The Electronic Transition Behavior Cr (III), Fe (III), Fe (II) and Ni (II), Transition Metal Cations In Ammonium Alum-Urea Room Temperature Ionic Liquid - Al-Qudsi, Zena N; Abood, Hadi M A (Al-Nahrain Journal of Science, 2013)
Some transition metal cations, Cr (III), Fe (III), Fe (II) and Ni (II), were soluble in the new alum/urea ionic liquid and found to coordinate to it with weak coordination bond. This was reflected by the change of strength of the electronic spectra of the cations or the nature of these spectra as with Fe (II) when it showed high spin and low spin with nitrite and thiocyanate ions. It was also observed that water molecules of the solid composition of ionic liquid were not free in ionic liquid particularly when metal cations electronic behavior were compared to those in aqueous solution. Basic species of ionic liquid were suggested to have weak ionic strength.